KOMUNIKASI DAN PERUBAHAN SOSIAL DALAM TRADISI PASIDIKARAN MASYARAKAT HINDU LOMBOK - Wirdiata, I Made Sri; Sutama, I Wayan (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2023)
Humans are social creatures who live better by interacting. Globalization brings significant changes in various aspects of individual and group life. This study aims to analyze social changes related to social changes in terms of the use of technology, community participation, and changes in the understanding of values and interpretations of religious teachings in the modern era. This study uses a qualitative method with a phenomenological approach. The results of the research show that there are changes and shifts in tradition. This tradition has experienced the dynamics of social change which can be seen from the attitudes and behaviour of the members of the sidikara. which have positive and negative impacts. Social changes in social relations tend to be materialistic individualists. In the use of technology, sidikara member relations show an increase in intensity, but the quality is not effective. In the context of understanding and interpreting religious teachings, it shows the euphoria of changing perspectives and expanding the meaning that brings religion into the individual realm and the profane realm simultaneously.